GENDER AND SOVCIAL CHANGE (FIELD STUDY) - Majida Shaker Mahdi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to know of Gender movements emerged with the emergence of the modern era, specifically with the outbreak of the French Revolution and the accompanying slogans of freedom and equality, and began to crystallize more clearly with scientific and cognitive progress, and Feminist movements have emerged as a reaction to male domination, as these movements are political and social in nature, aiming to criticize and analyze the reality of women for the injustice and persecution that she was exposed to throughout history through her criticism of the intellectual theses that placed women in the inferior position so that the man is the master. The goal of feminist movements is to free women from male domination and domination within the family in particular, and all forms of oppression and social and political violence in general. These movements were not limited to their activities in the regions in which they originated, i.e. the West, but rather found their way into the rest of the world, especially in the Arab world. This research is a process of surveying the history of these movements and knowing the stages of their development and the obstacles and successes that accompanied them from their inception to the present day, with a focus on those movements in the Arab and Iraqi world in particular. Herself a century or half a century ago, customs and traditions have narrowed and expanded from one period to another, and today they carry another form with the entry of technology and its continuous and easy connection with the world, as well as the level of education that was provided to them more than before, and which made her ideas special seriously. D is almost completely different from what it was in previous periods. Also, this research focuses on knowing the impact of feminist movements on the value change of women, as it seeks to identify the ideas brought about by these movements that have contributed to changing the values of women, and also seeks in particular to know the extent of the impact of these movements on Iraqi women, And the extent of the value change you brought about.